Experiment of oxygenated fuel on diesel engine: Performance, emission and particulate matter - Hazman, Abu Hassan; R., Mamat; Hagos, F. Y.; Najafi, G. (Penerbit UNIMAP, 2020)
The main purpose of the study is to characterise the effects of diesel, biodiesel blends B5M10 and B10M10 and emulsion fuels B5M10E3 and B10M10E3 as fuels for the impact on particulate matter emission. Engine tests have been performed to obtain results of engine performance, gas emission and particulate matter with various cycles. Excel analysis methods were used to analysethe data obtained.The B5M10E3 produces lower